A relação dos pilares de ESG com as normas de declaração de recursos e reservas minerais, segundo a regulamentação S-K 1300 - Carolina Cardoso Takano (2022)
In the mining sector, more specifically in publicly traded companies listed on stock exchanges, there is an obligation to prepare Public Reports on their entire mineral value chain. Such reports have legal obligations, under the guidelines of the International Codes of Public Declarations of Results of Mineral Exploration, Mineral Resources and Mineral Reserves, with the objective of reporting to their respective investors various aspects related to the matter. The preparation of this report is based on the pillars of transparency, materiality, and competence. This dissertation explains the acronym ESG, which originates from Environmental, Social and Governance and the purposes of these guidelines according to the UN direction, making it possible to understand the extreme relevance of the topics in question for the entire global market. The objectives and guidelines of the main International Codes were exposed, to understand the existing coherence and global connection on the subject. A specific code was chosen, which is propagated in the Code of Federal Regulations of the United States, regarding mineral declarations from registrants on the New York Stock Exchange. The relevant part of the code is called the S-K 1300 Regulation. An analysis was developed to be able to quantify which subsections of the S-K 1300, foreseen in this code, are related to ESG aspects. These points were also identified in one of the Public Reports of the company Nexa Resources S.A., a global miner of polymetallics, called Form 20F.